Market solutions in poverty : the role of microcredit in development countries with financial restrictions - Gómez Olivares, Mário (2010)
The creation of credit markets in poor countries is a crucial factor for their development. If well put into practice, people would be able to improve their quality of life. With the suitable support they will become educated and that will allow them to enlarge their business, to think by themselves and to appreciate that they have rights. Microfinance has seen great changes in the last 50 years and has become visibly known due to the success of some occurrence in developing countries and more recently in Europe through a number of schemes that have been implemented solving this key issue. In this article we discuss this experience, we evaluate the economic theory of microfinance and propose a alternative model. We conclude that microcredit can be see as a new approach in developing policies or as a scheme against unemployment.